The Luftwaffe : a study in air power 1933-1945 - Hooton, E. R. (Hersham, Surrey, U.K. : Classic, 2010)
There has not been an in-depth history of the Luftwaffe published for many years and this scholarly one-volume survey of the history of the Luftwaffe will become the leading reference work on the subject. The author is a well-respected military, aviation, and naval historian who has been researching this subject for many years in order to bring the latest information on and analysis of the Luftwaffe together in this work of reference. The book covers the history, campaigns, strategies, commanders, and personalities of the Luftwaffe in depth, as well as looking at the aircraft, although it does not cover aircraft types in detail. Among the specific areas covered are the prewar development of the Luftwaffe from its beginnings in the early 1930s, the attack on Poland in 1939, the campaigns in the west in 1940, the Battle of Britain, and the Mediterranean and North African campaigns up to 1942 and 1943.
Died in war -- born in peace -- A sword over Europe -- The shadow of Douhet -- Gripping the throat -- Duel in the West -- Icarus -- Crusade in the East -- the shield cracks and the sword breaks -- Endgame in the East and South -- Endgame in the West.
Includes bibliographical references (pages 270-287) and index.
Keywords: Germany. -- Luftwaffe -- History; 1939-1945; Geschichte 1933-1945; World War, 1939-1945 -- Aerial operations, German; Military operations, Aerial -- German; Luftwaffe; History